Histogenetic Radial Models as Aids to Understanding Complex Brain Structures: The Amygdalar Radial Model as a Recent Example - Garcia-Calero, Elena; Puelles, Luis (Frontiers in Neuroanatomy, 2020)
The radial dimension expands during central nervous system development after the proliferative neuroepithelium is molecularly patterned. The process is associated with neurogenesis, radial glia scaffolding, and migration of immature neurons into the developing mantle stratum. Radial histogenetic units, defined as a delimited neural polyclone whose cells share the same molecular profile, are molded during these processes, and usually become roughly stratified into periventricular, intermediate, and superficial (subpial) strata wherein neuronal cell types may differ and be distributed in various patterns. Cell-cell adhesion or repulsion phenomena together with interaction with local intercellular matrix cues regulate the acquisition of nuclear, reticular, or layer histogenetic forms in such strata. Finally, the progressive addition of inputs and outputs soon follows the purely neurogenetic and radial migratory phase. Frequently there is heterochrony in the radial development of adjacent histogenetic units, apart of peculiarities in differentiation due to non-shared aspects of the respective molecular profiles. Tangential migrations may add complexity to radial unit cytoarchitecture and function. The study of the contributions of such genetically controlled radial histogenetic units to the emerging complex neural structure is a key instrument to understand central nervous system morphology and function. One recent example in this scenario is the recently proposed radial model of the mouse pallial amygdala. This is theoretically valid generally in mammals (Garcia-Calero et al., 2020), and subdivides the nuclear complex of the pallial amygdala into five main radial units. The approach applies a novel ad hoc amygdalar section plane, given the observed obliquity of the amygdalar radial glial framework. The general relevance of radial unit studies for clarifying structural analysis of all complex brain regions such as the pallial amygdala is discussed, with additional examples.